2013
DOI: 10.1597/12-094.1
|View full text |Cite
|
Sign up to set email alerts
|

Early Mother-Child Interaction and Later Quality of Attachment in Infants with an Orofacial Cleft Compared to Infants without Cleft

Abstract: Objective : The main objective of this study was to assess mother-child patterns of interaction in relation to later quality of attachment in a group of children with an orofacial cleft compared with children without cleft. Design : Families were contacted when the child was 2 months old for a direct assessment of mother-child interaction and then at 12 months for a direct assessment of the child's attachment. Data concerning socioeconomical information and posttraumatic stress symptoms in mothers were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…This result may be either related to the fact that parental representations were not related to parenting style, which is obviously not the case as results of this study found correlations between the two (Authoritarian style was related to Negative Affective Experience with the child, and Authoritative style was related to Global Codes) and that a large literature already linked the two (eg, Bornstein 2001), or to the small sample size resulting in a lack of power, preventing the identification of small differences across groups in representations. Anyway, the fact that mothers of children with a cleft were more Authoritarian is supported by indirect previous evidence reporting that mothers of children with a cleft were in general less sensitive during interaction with their child (Nelson et al, 2012; Habersaat et al, 2013b). Therefore, it is possible that this general lower sensitivity toward the child leads to a more controlling or punitive parenting style.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…This result may be either related to the fact that parental representations were not related to parenting style, which is obviously not the case as results of this study found correlations between the two (Authoritarian style was related to Negative Affective Experience with the child, and Authoritative style was related to Global Codes) and that a large literature already linked the two (eg, Bornstein 2001), or to the small sample size resulting in a lack of power, preventing the identification of small differences across groups in representations. Anyway, the fact that mothers of children with a cleft were more Authoritarian is supported by indirect previous evidence reporting that mothers of children with a cleft were in general less sensitive during interaction with their child (Nelson et al, 2012; Habersaat et al, 2013b). Therefore, it is possible that this general lower sensitivity toward the child leads to a more controlling or punitive parenting style.…”
Section: Discussionmentioning
confidence: 83%
“…The objective of the present study was to assess maternal representations of their infants at age 2 months (before the reconstructive surgery), 12 months (after surgery), and 5 years when school starts in children born with and without an orofacial cleft. According to previous studies (Field and Vega-Lahr, 1984; Dolger-Hafner et al, 1997; Skrivan-Flocard and Habersaat, 2009; Despars et al, 2011; Bolomey et al, 2013; Habersaat et al, 2013b), we expected that mothers of children with a CL±P would show more negative emotions, be less sensitive, and perceive their child as being more difficult before the surgeries, compared with mothers of children without a cleft. After surgeries, differences between groups in terms of maternal representations were no longer expected.…”
Section: Research Aims and Hypothesesmentioning
confidence: 90%
See 1 more Smart Citation
“…Sitzman et al (2016) performed a systematic review of unilateral cleft lip aesthetic outcomes and subsequent revision surgeries as a surrogate for burden of care. Other studies have assessed specific psychological factors following the birth of a child with a craniofacial difference such as the motherchild interaction and the stability of the parental relationship (St John et al, 2003;Despars et al, 2011;Habersaat et al, 2013). Burden of care, however, must not be mistaken with the epidemiological concept of "burden of disease."…”
Section: Introductionmentioning
confidence: 99%
“…Sitzman et al (2016) performed a systematic review of unilateral cleft lip aesthetic outcomes and subsequent revision surgeries as a surrogate for burden of care. Other studies have assessed specific psychological factors following the birth of a child with a craniofacial difference such as the mother–child interaction and the stability of the parental relationship (St John et al, 2003; Despars et al, 2011; Habersaat et al, 2013). Burden of care, however, must not be mistaken with the epidemiological concept of “burden of disease.” This has been previously estimated by global prevalence and incidence, in addition to attributable fraction (the amount of a disease that can be attributed to a specific risk factor), years lost of life, years lived with disability, and disability-adjusted life years (Steenland and Armstrong, 2006; Global Burden of Disease Study 2016 Collaborators, 2017).…”
Section: Introductionmentioning
confidence: 99%